2008
DOI: 10.1063/1.2857478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystalline morphology on the tensile properties of electrospun polymer nanofibers

Abstract: Crystalline morphology of electrospun polymeric nanofibers strongly influences the mechanical properties. In this study, electrospun polycaprolactone nanofibers with smaller diameters that are produced from dilute polymer solutions have a higher degree of molecular orientation, crystallinity, stiffness, and strength, but lower ductility. Nanofiber diameter and the resulting crystalline morphology is influenced by whether complete crystallization of polymer chains took place before or after the electrospinning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
197
2
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(225 citation statements)
references
References 22 publications
20
197
2
6
Order By: Relevance
“…SEM micrographs showed that in all cases microfibers had extremely rough surfaces with characteristic transversal striations whereas unloaded nanofibers showed relatively smooth surfaces that became rough with pores when triclosan was incorporated. The texture of microfibers suggests a dense lamellar stacking perpendicular to the fiber axis with amorphous regions between them [18].…”
Section: Results and Discussion 31 Morphology Of Electrospun Polylamentioning
confidence: 99%
“…SEM micrographs showed that in all cases microfibers had extremely rough surfaces with characteristic transversal striations whereas unloaded nanofibers showed relatively smooth surfaces that became rough with pores when triclosan was incorporated. The texture of microfibers suggests a dense lamellar stacking perpendicular to the fiber axis with amorphous regions between them [18].…”
Section: Results and Discussion 31 Morphology Of Electrospun Polylamentioning
confidence: 99%
“…An interesting work about the effect of crystallinity of PLA microfiber by electrical and centrifugal field on mechanical responses was described by Liao et al [8]. Lim and Tan reported that electrospun polycaprolactone (PCL) nanofibers with smaller diameters had a higher degree of molecular orientation, crystallinity and mechanical properties [9]. In other paper, Tan and Lim reported the effect of annealing on electrospun poly(L-lactic acid) (PLLA) about crystalline structure after electrospinning [10].…”
Section: Introductionmentioning
confidence: 96%
“…40,43 Molecular structure X-ray diffraction is commonly used to determine the crystal structure of polymer fibers. 15,20,42,52 Often after chemical modification or the attachment of functional groups, the molecular structure is determined using FTIR 42,43,85,86 or nuclear magnetic resonance analysis. 52 …”
Section: Drug and Protein Distributionmentioning
confidence: 99%